Os habitantes do rio e as missões religiosas no sertão pernambucano: uma arqueologia da paisagem fluvial do Rio São Francisco – Orocó - Oliveira, Jessica Rafaella de (2016)
At the beginning of the portuguese "colonization", the valley of São Francisco was inhabited by various indigenous peoples, and it is through the accounts of travelers and missionaries we can get the first informations about their settlements and way of life. The indigenous space in the Médio São Francisco, when the colonizers arrived, was composed of populations generally called by the chroniclers of Tapuias and Cariris. The indoctrination work in the region were initiated by the seventeenth century, the early missions dating back to 1671. Many documents and missionaries's passages records through the area, prove the existence of villages on the islands of São Francisco river, located in the area currently known as Submedio. The island of Santa Maria, for example, was the scene of a large village that thrived during the seventeenth and eighteenth centuries, and this insular unit still has part of the old architectural park in ruins, especially its main religious equipment. Within this context the present research, turns to studies of contact and religious missions, however distanced himself from the approaches of Archaeology missionary directed only to understand the missions as acculturation agents, but above all, enhancing the role of indigenous within a process of transculturation and active agents in the social constructions. Results from a thorough literature revision, specific interventions in the field and an approach to archeology of the landscape, as well as a missionary archeology and indigenous history. Sought in this sense, understand what were the religious missions that made the Submedio São Francisco, major routes of indigenous indoctrination, and how they contributed to the consolidation of the different landscape elements which are of fundamental importance not only to fill the gaps in particular history of the islands, but to understand the dynamics of occupation of the region as a whole.